Assessment of Yard Long Bean Varieties for Optimal Cultivation in Tropical Conditions (Research in Agriculture Livestock and Fisheries, 2024)
Yard long bean (Vigna unguiculata) is an important leguminous crop in tropical countries. It is a very common vegetable cultivated by the farmers of the South Asian countries including Bangladesh. The popularity of this vegetable is increasing due to its good taste and nutritive value. An experiment based on Randomized Complete Block Design (RCBD) with three replications was conducted at the Agricultural Research Field, Noakhali Science and Technology University, Noakhali, Bangladesh, from October 2021 to December 2021 to evaluate the growth and yield performance of four varieties of yard long bean. The varieties were FLK-203, FLK-204, FLK-205, FLK-206. The study revealed that the highest plant height (261.8) was recorded in the Yard-long bean FLK-206 followed by FLK-203 (239.1). The first flowering (31.33 DAP) was found in variety FLK-203 followed by variety FLK-204 (36 DAP). The highest number of pods plant-1 (25.33) was found in Yard long bean variety FLK-204 followed by variety FLK-206 (18.33) plant-1. Maximum fruit length (67.56 cm) was recorded in variety FLK-206 followed by yard-long bean variety FLK-204 (56.16). The highest pod girth (1.06 cm) was in the yard long bean variety FLK-203 followed by FLK-204 (0.8 cm). Maximum number of seed pod-1 (20.66) was found in variety FLK-203 followed by FLK-206 (18.66). The highest weight of 10 seeds (2.21) was found in variety FLK-206 followed by variety FLK-204 (1.16). The highest fresh weight pod-1 (32.4 gm) was in the yard long bean variety FLK-203 followed by FLK-204 (24.23 gm). The highest yield pod-1 (690.26 gm) was in yard-long bean variety FLK-203 followed by FLK-206 (506.2 gm). The highest pod yield ha-1 (82.73 t ha-1) was recorded in yard-long bean FLK-203 followed by FLK-206 (60.73 t ha-1). So, the variety Yard long bean FLK-203 was found superior based on the overall performance for cultivation under the Argo-climatic condition of Noakhali.Vol. 10, No. 3, December 2023: 269-276